Effects of weather on average daily gain and profitability - D.R. Mark; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 2002)
The effect of several weather conditions on average daily gain (ADG) and profits is quantified for typical steers and heifers fed in commercial feedyards in Western Kansas from 1980 to 1999. ADG predictions for particular pens of cattle are often used to plan marketing dates and calculate breakeven purchase prices. Weather is known to influence cattle performance, and expected weather conditions can be used to improve ADG predictions. Effects on ADG and profits from combinations of, and interactions between, temperature, precipitation, humidity, and wind speed were analyzed. The influence of these weather conditions was allowed to differ by sex, placement weight, and placement month. Results indicate that performance and profits of lightweight placements are more sensitive to temperature and precipitation changes than are heavier weight calves. Above average temperature tends to reduce cattle performance during the summer and increase it for cattle fed during the winter.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Cattle performance; Average daily gain; Cattle feeding profits; Temperature; Weather